2019 Expert opinion on biological treatment use in inflammatory bowel disease management - Törüner, Murat; Akpınar, Hale; Akyüz, Filiz; Dağlı, Ülkü; Över Hamzaoğlu, Hülya; Tezel, Ahmet; Ünsal, Belkıs; Yıldırım, Süleyman; Çelik, Aykut Ferhat (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Törüner M, Akpınar H, Akyüz F, et al. 2019 Expert opinion on biological treatment use in inflammatory bowel disease management. Turk J Gastroenterol 2019; 30(Suppl 4): S913-46.